Pricing strategies : a marketing approach - Schindler, Robert (Los Angeles, Calif. : Sage Publications, Inc, 2012)
'The primary theme of Pricing Strategies is that pricing should be guided by the marketing concept, which indicates that success is achieved through a focus on the needs and sensitivities of the customer. This customer-focus theme is evident throughout the text. The author helps to overcome the mathematical anxieties of students with an intuitive approach to understanding basic pricing concepts, and presents mathematical techniques as simply more detailed specifications of these concepts'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Pricing; Marketing